2003
DOI: 10.1523/jneurosci.23-01-00269.2003
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Modulation of Synaptic Plasticity

Abstract: Unlike the proposed role of reactive oxygen species in neurodegeneration, acute effects of reactive oxygen on synaptic plasticity are poorly understood. Using rat hippocampal slices, we found that exposure to a high concentration (0.5-5 mm) of H(2)O(2) reduces EPSPs in both potentiated and nonpotentiated synapses. Exposure of the slices to 20 microm H(2)O(2) did not affect expression of preestablished long-term potentiation (LTP) but prevented induction of new LTP and enhanced long-term depression (LTD). Surpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
148
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(160 citation statements)
references
References 43 publications
12
148
0
Order By: Relevance
“…24 Following hyperoxia, we detected an acute and long-term dysregulation of SYN1, a protein that regulates nerve terminal function in mature synapses and also affects axonogenesis and synaptogenesis. 26 While the acute dysregulation of SYN1 may be interpreted as secondary to a depletion of synaptic vesicles, the increase in abundance of two isospots of this protein 4 weeks following hyperoxia suggests a long-term disruption of normal synaptic function.…”
Section: Synaptic Function and Vesicle Traffickingmentioning
confidence: 94%
See 1 more Smart Citation
“…24 Following hyperoxia, we detected an acute and long-term dysregulation of SYN1, a protein that regulates nerve terminal function in mature synapses and also affects axonogenesis and synaptogenesis. 26 While the acute dysregulation of SYN1 may be interpreted as secondary to a depletion of synaptic vesicles, the increase in abundance of two isospots of this protein 4 weeks following hyperoxia suggests a long-term disruption of normal synaptic function.…”
Section: Synaptic Function and Vesicle Traffickingmentioning
confidence: 94%
“…In the mature brain, oxidative stress modulates neuronal excitability and morphological features of synapses: 24,25 while low levels of hydrogen peroxide seem to prime synapses and induce long-term potentiation (LTP), high levels of ROS have detrimental effects on neuronal plasticity and suppress LTP in hippocampal slices of rats and mice. 24 Following hyperoxia, we detected an acute and long-term dysregulation of SYN1, a protein that regulates nerve terminal function in mature synapses and also affects axonogenesis and synaptogenesis.…”
Section: Synaptic Function and Vesicle Traffickingmentioning
confidence: 99%
“…In contrast, others have shown that rapamycin impairs LTP by inhibiting mTOR through reduced protein synthesis (Casadio et al, 1999;Tang et al, 2002). Finally, a third study demonstrated that rapamycin did not affect LTP at baseline, and did not prevent the inhibition of LTP by H 2 O 2 (20 µM) (Kamsler and Segal, 2003).…”
Section: Introductionmentioning
confidence: 94%
“…A low concentration of H 2 O 2 (1 M), a molecule that partially mediates superoxide-induced potentiation (Knapp and Klann 2002), increased the magnitude of LTP (Kamsler and Segal 2003). This effect was dependent on activation of L-type calcium channels but not NMDA receptors (Kamsler and Segal 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A low concentration of H 2 O 2 (1 M), a molecule that partially mediates superoxide-induced potentiation (Knapp and Klann 2002), increased the magnitude of LTP (Kamsler and Segal 2003). This effect was dependent on activation of L-type calcium channels but not NMDA receptors (Kamsler and Segal 2003). Furthermore, a functional coupling between RyRs and L-type calcium channels has been established in the dentate gyrus and cerebellar granule cells (Chavis et al 1996;Welsby et al 2006).…”
Section: Introductionmentioning
confidence: 99%